2019
DOI: 10.21037/atm.2019.11.126
|View full text |Cite
|
Sign up to set email alerts
|

Gentiopicroside (GENT) protects against sepsis induced by lipopolysaccharide (LPS) through the NF-κB signaling pathway

Abstract: Background: Sepsis is a high-mortality disease without effective therapeutic options. The hyperactivation of the monocyte-macrophage system, especially M1 macrophages, triggers the onset of septic shock. Gentiopicroside (GENT), the main active component in the traditional Chinese medicinal herb Radix Gentianae, has been shown to have anti-inflammatory properties. Nevertheless, this anti-inflammatory effect has not been fully elucidated.Methods: In vitro, we stimulated primary bone marrow-derived macrophages (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…A previous study elucidated that NLRP3 and NLRP4 work to regulate production and pyroptosis of IL-18 and IL-1β, thus testifying that NLCR4 silencing causes the inhibition of IL-1β, which is in accordance with our findings [ 31 ]. A prior study also noted that gentiopicroside conferred protection against shock and decreased inflammatory cytokine production of IL-1β, IL-6 and TNF-α in lung tissues [ 32 ]. Given the above key findings, it is reasonable to regard silenced NLRC4 as an important gene when inhibiting inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study elucidated that NLRP3 and NLRP4 work to regulate production and pyroptosis of IL-18 and IL-1β, thus testifying that NLCR4 silencing causes the inhibition of IL-1β, which is in accordance with our findings [ 31 ]. A prior study also noted that gentiopicroside conferred protection against shock and decreased inflammatory cytokine production of IL-1β, IL-6 and TNF-α in lung tissues [ 32 ]. Given the above key findings, it is reasonable to regard silenced NLRC4 as an important gene when inhibiting inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the expression of MMPs could be changed via the PI3K/AKT pathway (42). NF-κB is a downstream protein of the PI3K/AKT pathway and can regulate the secretion of MMP (20), with inhibition of NF-κB reducing the secretion of MMP (43). The p-PI3K and p-AKT are phosphorylated activated forms of PI3K and AKT (44).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K/AKT pathway increases production of MMPs through a variety of downstream target proteins. Nuclear factor (NF)-κB is one of the target proteins of the PI3K/AKT pathway and is also a key regulator of MMP production as a transcriptional factor (20). The PI3K/AKT pathway is also associated with tumor necrosis factor (TNF)-α-induced activation of OA fibroblast-like synoviocytes, which may be involved in the pathogenesis of OA (21).…”
Section: Introductionmentioning
confidence: 99%
“…Secoiridiods are characteristic substances of MR, while their contents are very low. Studies have indicated that secoiridiod glycosides possess wide biological activities such as anti-inflammatory and immunoregulatory ( Saravanan et al, 2014a ; Saravanan et al, 2014b ; Wang et al, 2019a ), analgesic ( Liu et al, 2016 ; Garrido-Suárez et al, 2020 ), anti-tumor ( Tang et al, 2019 ; Xiao et al, 2020 ) hepatoprotective ( Shao et al, 2017 ; Wu et al, 2017 ), hypoglycemic ( Vaidya et al, 2013a ; Dhanavathy, 2015 ; Vaidya et al, 2012 ; Vaidya et al, 2009 ), neuroprotective ( Wang et al, 2019b ; Wu et al, 2019 ) effects.…”
Section: Phytochemistrymentioning
confidence: 99%